Do Microcredentials Help New Workers Enter the Market? Evidence from an Online Labor Platform - Kässi, Otto; Lehdonvirta, Vili (University of Wisconsin Press, 2025)
We investigate the effects of a voluntary microcredentialing scheme on an online freelancing labor market. Drawing on transaction-level data, we show that obtaining a microcredential increases workers’ earnings. This effect is not driven by increased worker productivity but by decreased employer uncertainty. The increase in worker earnings is realized through an increase in the value of the projects won rather than an increase in the number of projects. We also find that the effect of microcredentials is lower for more experienced workers, which suggests that signaling by microcredentials and other forms of verified information are partial substitutes.